Pendekatan Kepemimpinan Kependidikan Al-Ghazali dan Ibnu Khaldun: Relevansi dalam Manajemen Agile Modern - Pratiwi; Iswan (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Leadership is an individual's personal ability that plays an important role in bringing the organisation to its goals. The complexity of the environment of modern society, along with the pressure of competition between educational institutions, the increasing expectations of parents and the need to introduce changes in the process of working in Islamic educational institutions led to a great deal of interest in agile management methods. Al Ghazali and Ibn Khaldun are great figures who pay great attention to the world of education, including the concept of educational leadership. The presence of leaders in facing these conditions is absolutely necessary so that Islamic educational institutions can still exist to contribute to the intellectual life of the nation. The purpose of this research is to examine the concept of educational leadership of Al-Ghazali and Ibn Khaldun and explain the relevance of these concepts in the context of agile management. This research uses the Library Research method. The author searches for literature sources in the form of books and journals. The analysis used is comparative analysis. The conclusion of this research is the relevance of the concept of educational leadership of Al-Ghazali and Ibn Khaldun in the context of agile management, namely working to achieve the pleasure of Allah swt, holding fast to the goals of Islamic education, having leadership skills, involving customers in educational projects, involving customers in educational projects, teamwork and collaboration, new work processes, regular reflection and continuous quality improvement.